2010
DOI: 10.1177/003335491012500109
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination and Mental Health Problems among Homeless Minority Young People

Abstract: Intervention programs that contextualize discrimination and enhance racial/ethnic identification and pride among homeless young people are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…There is also an overlap of other forms of racial, generational and sexual orientation. Milburn et al (2010) studied adolescents living on the streets in Los Angeles, finding racial discrimination values ranging from 12% in whites and 42% among Latino immigrants. In the group studied racial discrimination was reported by 36% of respondents.…”
Section: Discussionmentioning
confidence: 99%
“…There is also an overlap of other forms of racial, generational and sexual orientation. Milburn et al (2010) studied adolescents living on the streets in Los Angeles, finding racial discrimination values ranging from 12% in whites and 42% among Latino immigrants. In the group studied racial discrimination was reported by 36% of respondents.…”
Section: Discussionmentioning
confidence: 99%
“…Milburn and colleagues (2010) found that perceptions of racial/ethnic discrimination were associated with heightened levels of emotional distress among homeless adolescents in Los Angeles, and that foreign‐born Hispanic persons in this group reported the highest levels of perceived discrimination. Since a positive identification with one's racial/ethnic group has been shown to reduce emotional distress for members of minority groups, the authors suggested that mental health programs be designed for these youth to “build upon racial ethnic/identification and pride” (Milburn et al, , p. 66). This study provides evidence that the physical and mental health risks that homeless youth face are related to racial, ethnic, and gender discrimination.…”
Section: Race and Youth Homelessnessmentioning
confidence: 99%
“…Low performance or school drop-out (15,17,36,38,48) Bdo abandonoenho escolar.gais); ullying (18,36) Discrimination and racism experience that led to major emotional suffering (19,49) To belong to social-economic class D or E (12) University application processes as a stressful event (Vestibular) (30) Social pressure from partners and academic life (37) 22.6…”
Section: School Relatedmentioning
confidence: 99%